Assessing the Impact of International Financial Reporting Standards (IFRS) through Bibliometric Research - Loso Judijanto; Tri Widyastuti Ningsih; Indah Wati; Sri Adella Fitri (Eastasouth Institute, 2023)
The present study evaluates the influence of International Financial Reporting Standards (IFRS) on scholarly literature through the utilization of bibliometric analysis. This study examines the frequency of occurrence of terms in a dataset consisting of renowned publications, thereby uncovering significant themes and areas of focus in IFRS research. Prominent terminology such as